Bacterial screening in sweetpotato plantlets helps to identify microbial contaminants prior to in vitro mass multiplication - Gatimu, R. (2025)
This research brief outlines a laboratory protocol developed by the International Potato Center (CIP) and KEPHIS to reduce bacterial contamination in sweetpotato tissue culture. The study used a nutrient broth screening method to detect microbial contamination in in vitro plantlets before mass micropropagation. Conducted at the KEPHIS Plant Quarantine and Biosecurity Station (PQBS) in Nairobi, Kenya, the screening helped identify infected plantlets early, preventing contamination during culture multiplication. The method improved success rates, reduced losses of valuable genotypes, and enhanced overall lab efficiency. The brief emphasizes the importance of integrating bacterial indexing into standard tissue culture practices to safeguard plant health and ensure reliable production of clean planting materials.